Ecological and evolutionary variation in community nitrogen use traits during tropical dry forest secondary succession. Issue 5 (May 2016) - Bhaskar, Radika; Porder, Stephen; Balvanera, Patricia; Edwards, Erika J.
Abstract: We assessed the role of ecological and evolutionary processes in driving variation in leaf and litter traits related to nitrogen (N) use among tropical dry forest trees in old‐growth and secondary stands in western Mexico. Our expectation was that legumes (Fabaceae), a dominant component of the regional flora, would have consistently high leaf N and therefore structure phylogenetic variation in N‐related traits. We also expected ecological selection during succession for differences in nitrogen use strategies, and corresponding shifts in legume abundance. We used phylogenetic analyses to test for trait conservatism in foliar and litter N, C:N, and N resorption. We also evaluated differences in N‐related traits between old‐growth and secondary forests. We found a weak phylogenetic signal for all traits, partly explained by wide variation within legumes. Across taxa we observed a positive relationship between leaf and litter N, but no shift in resorption strategies along the successional gradient. Despite species turnover, N‐resorption, and N‐related traits showed little change across succession, suggesting that, at least for these traits, secondary forests rapidly recover ecosystem function. Collectively, our results also suggest that legumes should not be considered a single functional group from a biogeochemical perspective.